Synthesis and characterization of furan resin and their nanocomposites - Rivero, Guadalupe (2010)
Formaldehyde emissions are nowadays trying to be reduced because of its atmospheric pollutant character. Besides, it is encouraged the use of polymeric materials synthesized from biomass wastes as row materials. For this reason, furan resins would be an alternative to phenolic resins, where formaldehyde is replaced by furfural as a reactant. Regarding, the addition of nanoparticles to the furan resin should enhance their performance as metal coatings with good thermal and oxidative resistance. The aim of this article is to study the influence of the in situ addition of different type of nanoparticles on the chemical reactions involved in the synthesis of a furan resin. From the viscosity measurements it was observed that the addition of the nanoreinforcements led to a higher resin reaction rate. Differences in the final chemical structure among the materials were also observed by infrared spectroscopy analyses. chemical reactions involved in the synthesis of a furan resin. From the viscosity measurements it was observed that the addition of the nanoreinforcements led to a higher resin reaction rate.